Effects of thinning on diameter, heartwood, density and drying defects of gmelina arborea - Vallejos, Jonathan; Serrano, Rafael; Moya-Roque, Róger (Universidade Federal de Sao Carlos, 2015)
The effect of three levels thinning intensity in Gmelina arborea plantation on tree diameter, heartwood (diameter and percentage), wood density and drying defects (twist, crook, bow and check) was studied. Wood used for this study was obtained from eight-year-old plantations with thinning intensity of 60, 70 and 80% of initial density. Nine trees were selected from each trial. Results showed that tree diameter and wood density were similar in thinning intensity of 70 and 80%, but tree diameter from the plantation with 60% of thinning intensity was lower than plantation of 70 and 80%. Wood density of trees from 60% thinning intensity plantation was higher than 70 and 80%. Heartwood diameter and its percentage were the highest in 80% of thinning intensity. But not difference was found between 60 and 70% in heartwood (diameter and percentage). Finally, drying defects were not affected significantly by thinning intensity.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84936767024&partnerID=40&md5=9fbe4413725083bd95d865fc55b123c4
Keywords: Morfología; Maderas; Densidad; Propiedades; Plantaciones; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Product science::Wood fibre and forest products